Optimisation of 4D printed mortar-mini vascular networks (m-MVNs) for built heritage preservation - C. De Nardi; D. Gardner; J. Sweeney; A. Akkady (Materials & Design)
As climate change increases risks to heritage buildings, enhancing repair methods for historic masonry is essential. This paper presents the design and optimisation process for the manufacturing of a novel self-healing technology—named mortar mini-vascular networks (m-MVNs)—intended for installation in mortar joints during joint repair. m-MVNs are Fused Deposition Modelling (FDM)-printed polymer units with interconnected channels designed to store and protect healing agents. When damage in the mortar joint exceeds a threshold, the m-MVNs rupture, releasing the healing agent to initiate the self-repair process. Engineered within a 4D printing framework, the m-MVNs were optimised through iterative design refinement to protect healing agents, with fracture properties ensuring activation under specific stress conditions. The final m-MVN design, manufactured using adaptive slicing from clear polylactide acid (PLA), achieved the best performance in terms of: i) geometrical regularity, ii) mechanical compatibility with hydraulic lime-based mortars, iii) quasi-isotropy, iv) and watertightness. This breakthrough paves the way for innovative self-healing solutions in heritage conservation.